The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1063/1.4921314
|View full text |Cite
|
Sign up to set email alerts
|

Copper in Alzheimer’s disease: Implications in amyloid aggregation and neurotoxicity

Abstract: The relationship of copper dyshomeostasis with neurodegenerative diseases has become evident in the last years. Because of the major role that this metal ion plays in biological processes, most of which being located in the brain, it is not surprising that changes in its distribution are closely related with the advent of neurodegenerative disorders such as Alzheimer’s disease (AD). An increasing number of works have dealt with this subject in the last years, and opened an intense debate in some points while r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 101 publications
0
38
0
Order By: Relevance
“…The conditionalaffinity constants of the three peptides have been determined by intrinsic fluorescence measurements, and are two orderso fm agnitude highert han that previously reportedf or Ab . Competitive binding studies based on fluorescencem easurements using either Ab (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) or bacterial inclusionb odies of Ab42-GFP have confirmed their efficient ability to displace Ab-bound Cu II ions in an irreversible fashion. ThT emission studies have suggested that copper-induced oligomer aggregation of Ab is indeed inhibited in the presence of the peptides, and on adding the peptides to Cu-induced fibrils am odulation of such fibrillation occurred.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The conditionalaffinity constants of the three peptides have been determined by intrinsic fluorescence measurements, and are two orderso fm agnitude highert han that previously reportedf or Ab . Competitive binding studies based on fluorescencem easurements using either Ab (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) or bacterial inclusionb odies of Ab42-GFP have confirmed their efficient ability to displace Ab-bound Cu II ions in an irreversible fashion. ThT emission studies have suggested that copper-induced oligomer aggregation of Ab is indeed inhibited in the presence of the peptides, and on adding the peptides to Cu-induced fibrils am odulation of such fibrillation occurred.…”
Section: Resultsmentioning
confidence: 96%
“…As shown above, the three peptides exhibit Cu 2+ ‐binding affinities that are up to two orders of magnitude higher than that displayed by Aβ(1‐40). To confirm their higher proficiency to “capture” copper(II) ions, competitive binding experiments were performed using the non‐aggregating amyloid fragment Aβ(1‐16) ( K cond =1–2×10 7 m −1 ), following the intrinsic fluorescence of the tyrosine residue Tyr10 of the protein and the emission of a fluorescent tripeptide. For these studies, HK C H was preferred because its emission at 410 nm would not interfere with that of Aβ(1‐16) (emission of tyrosine at 305 nm); the excitation wavelength of HK c H is far enough from that of Aβ(1‐16), in contrast to that for HWH (λ exc =275, 300, and 280 nm for tyrosine, the coumarin group of HK C H , and tryptophan, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations